Passivation kinetics of a high nitrogen face-centered-cubic phase formed on AISI 304L austenitic stainless steel in borate buffer solutions by photo- and electrochemical methods. (20th October 2021) - Tong, S.; Che, H.L.; Wang, K.S.; Lei, M.K.
Highlights: Passive film thickening derived from transits current and photocurrent on γN phase. Passive films momentarily dissolved in borate buffer solutions with Ph = 6.5–7.7. Passive films continuously grew in the solutions with pH = 8.1–8.9 up to 8 h. Formation and dissolution kinetics on γN phase were simulated and explained by PDM. Transporting N in oxygen anion vacancy hydrolyzed to ammonia then to ammonium. Abstract: The passive film thickening on a high nitrogen face-centered-cubic phase (γN ) layer in a series of borate buffer solutions is in-situ characterized by the transient corrosion current and potential with the structure evolution in the photoelectrochemistry and electrochemical noise analyzes. The real-time nitrogen effect on the passivation is intended by controlling the proton concentration of the borate buffer solutions at the pH values of 6.5–8.9 with the immersion time up to 8 h. The γN phase layer on the nitrided AISI 304L austenitic stainless steel has a transitional maximum thickness with the firstly immersion time, and then gradually achieves a steady thickness value. Seven components, such as α-Fe2 O3, FeO, Cr(OH)3, γ-FeOOH, CrOOH, Cr2 O3 and γ-Fe2 O3, are observed with 8 h, although no CrNx and FeNx compounds are detected due to lack of references in photoelectrochemistry. The nitrogen dissolving from the γN phase layer in the borate buffer solutions is clarified, according to the real-time photocurrent and transient corrosion current at the controllable pH values . The passivation transition period dependent on the nitrogen dissolving in the borate buffer solutions is proposed by the point defect model. The nitrogen hydrolysis to ammonia with a fast reaction rate is determined by the nitrogen concentration on the surface of the γN phase layer. The ammonia is further hydrolyzed to ammonium with a lower reaction rate which is mainly affected by proton concentration in the solutions. Therefore, the two-step nitrogen hydrolysis from the γN phase layer is in - situ discovered as an effect mechanism in the borate buffer solutions. Graphical abstract: Image, graphical abstract